Determinants of science and social studies achievement: the interplay of motivation, parental involvement, and digital literacy - Suhariyanto; Onik Farida Ni’matullah; Roni Alim Ba'diyah Kusufa (Jurnal Pemikiran dan Pengembangan Sekolah Dasar (JP2SD), 2026)
The learning outcomes in the subjects of Natural and Social Sciences (IPAS) serve as a key indicator reflecting students' understanding of environmental and social phenomena, as well as a foundation for developing critical thinking and problem-solving skills in primary education in Indonesia. This study aims to analyze the influence of learning motivation, parental involvement, and digital literacy on the IPAS learning outcomes of upper-grade students at SD Negeri Tlontoraja 8, Pasean District, Pamekasan Regency. The hypothesis proposed in this study is that all three variables, both simultaneously and partially, have a positive and significant effect on student learning outcomes. This research uses a quantitative approach with an ex post facto design, which aims to test the relationships between variables without experimental manipulation. The sampling technique used is total sampling, involving 65 students as respondents. Data was collected through validated questionnaires and analyzed using multiple linear regression. The results show that learning motivation, parental involvement, and digital literacy simultaneously have a significant effect on IPAS learning outcomes (F = 493.206, p < 0.05, R² = 0.782). Partially, learning motivation (t = 7.886, p < 0.05), parental involvement (t = 4.528, p < 0.05), and digital literacy (t = 7.465, p < 0.05) each have a positive and significant effect. These findings emphasize that enhancing student learning motivation, parental involvement, and strengthening digital literacy are crucial strategies for improving students' conceptual understanding and academic achievement in IPAS learning at the primary school level.